The Effect of Training Material and Instructor on the Behavior of Graduates of Teacher Academy Program with Learning Outcome as Intervening Variable (Case Study at XYZ Company) - Sally Arianita Dewi; Ahmad Badawi Saluy (Dinasti Publisher, 2022)
This study aims to determine and analyze the effect of training material and instructor on the training graduates’ behavior with learning outcome as an intervening variable in Teacher Academy batch 3 program at XYZ company. Learning outcome and behavior are level 2 and 3 of Kirkpatrick evaluation model. The method used in this research is descriptive quantitative research with a causal relationship approach. The population in this study is the participants of Teacher Academy batch 3 program. The number of samples in this research is 100 respondents. Data analysis is done using Structural Equation Model (SEM) with SmartPLS (Partial Least Square) 3.0. The results show that there is a positive and significant effect of training material on participants’ learning outcome, a positive and significant effect of training instructor on participants’ learning outcome, a positive and significant effect of training material and training instructor on participants’ learning outcome, and a positive and significant effect of participants’ learning outcome on the training graduates’ behavior. Learning outcome can mediate the effect of training material and instructor on the training graduates’ behavior.